Antimutagenic effects of expressions from twelve medicinal plants - Lim-Sylianco, C.Y; Concha, J.A; Jocano, A.P; Lim, C.M (1986)
Mitomycin C, tetracycline hydrochloride and dimethylnitrosamine induced the formation of micronucleated polychromatic erythrocytes in bone marrow cells of experimental mice. This indicates that these three systems are mutagenic and clastogenic. The formation of micronucleated polychromatic erythrocytes induced by mitomycin C was greatly reduced by expressions prepared from fruits of Momordica charantio Linn., Persea americanaMill., Syzygium cumini (Linn.) Skeels, Pithecellobium dulce (Roxb) Benth., Averrhoa bilimbi Linn.,Cucumis melo Linn., Carica papaya Linn., Cucurbita maxima Duchesne, Spondias purpurea Linn.,Citrus decumana Linn, and Lycopersicon lycopersicum (Linn.) Karsten. The same observations were made of expressions from roots and seeds of Raphanus sativus Linn. From flowers and leaves of C. maxima, from leaves of M. charansia, and from secds of C melo, the same systems also reduced micronuclei formation as induced by tetracycline hydrochloride. The induction of micronuclei formation by dimethylnitrosamine was significantly reduced by expressions from fruits of M. charantia, A. bilinbi, C. melo, C. papaya, C. maxima and L. lycopersicum. The same observations were made with expressions from leaves of M. charantia, roots of R. sativus and seeds of C. melo, when heated, expressions from plants still reduced micronuclei formation as induced by mitomycin C and tetracycline. The extent of reduction, however, was significantly decreased when expressions of the following were boiled: M. charantia fruit and leaves, C maxima flowers and fruits, L.lycopersicum fruits.